ANALISIS CASH FLOW DALAM RANGKA MENINGKATKAN PROFITABILITAS PADA KOPERASI NILA KANTI DINAS KOPERINDAG KOTA BIMA - Megasuciati Wardani (Universitas Dian Nuswantoro, 2022)
The aim of this research is to find out how the cash flow is at the Nila Kanti Cooperative (Dinas Koperindag) in Bima City. The type of research used in the research is descriptive research. This research describes the variable The Nila Kanti Cooperative (Dinas Diperindag) of Bima City was established from 2005 to 2022. The sample in this research is the financial report of the Nila Kanti Cooperative (Dinas Koperindag) of Bima City from 2015 to 2022. The results of the research show that cash flow will increase The profitability of the Nila Kanti Cooperative (Dinas Koperindag) Bima City is above the Profit Quality Ratio standard of 1, which reflects that the cash position of the Nila Kanti Cooperative is optimal in increasing its profitability, where by using the one sample t test, the t value is calculated is smaller than the t table value, so what is accepted is the null hypothesis, namely the assumption that the cash flow to increase profitability at the Nila Kanti Cooperative (Dinas Koperindag) Bima City is above the standard profit quality ratio. The results of the one sample t test obtained a tcount value of 2.389 and a ttable of 1.533. By comparing the tcount and ttable values, it turns out that the tcount value is greater than ttable (2.389>1.533). So the alternative hypothesis (Ha) which reads